Jihad Menurut Pola Pikir Syekh Muhammad Abu Bakar Syatha Dalam Kitab I’anatut Thalibin (Perang Bukan Tujuan Utama) - Ishom Fuad, Muhammad (LP3M Universitas Al-Qolam Malang, 2024)
This research is motivated by the existence of a misunderstanding among the public regarding the meaning of jihad. In general, when the word